Senegalese students in France and salaried work: the "student job" as the key to reading a migration in crisis? - (:unkn) unknown (My University, 2021)
The place that wage labour has taken in the history of West African student migration to France still seems to us largely unknown. However, it can provide a new and original lens through which to view the figure of the West African student in France. In Senegal, for example, the economic crisis of the 1970s led to a reduction in the number of grants awarded by the state to students abroad, which, over time, resulted in an increasing number of students without state aid or scholarships having to resort to a ‘student job’ in order to live in France. Thus, the study of the place of ‘student jobs’ in the paths of these students has led to two new analyses of the realities of these African students in France. Firstly, showing how the ‘student job’ has progressively become a marker of proletarianisation and continuous degradation of their living conditions in France. And secondly, showing how it has ended up becoming one of the main markers of social differentiation between Senegalese students in France. This work is based on the analysis of the results from my master’s and doctoral research in sociology between 2013 and 2020, which focused on the migratory paths of Senegalese students in France.
Keywords: African Research